A Principled Design of Intelligent Agent for the SLA negotiation process in cloud computing - Kumar, R. (Institute of Electrical and Electronics Engineers Inc., 2022)
Cloud Service Providers (CSPs) are in massive demand with the growing field of information technology. CSP produces enormous solutions and support for cloud, IoT, Fog, and Edge computing. In the current era of the competitive cloud market, consumer satisfaction plays an important role. Quality of Services (QoS) fulfilment for service level agreement (SLA) for CSP and consumers is always given more attention. Consumers face problems over resource delivery after signing SLA and CSP issues to provide over-demanded resources. In the dynamic market of cloud and heterogeneous environments, the existing system needs an intelligent agent-based negotiation system (IANS) to handle responsibilities. IANS will perform the negotiation process and measure the key factors to make fast decisions with maximum utility value at an affordable price. IANS uses a behavioural learning analysis algorithm between consumers and CSP to select a reliable, secure server at a minimum cost. The negotiation process will be using metrics, performance factors, evaluation measures, and behaviour learning for decision making. Â© 2022 IEEE.